Hubungan indeks pembangunan manusia dan pengangguran dengan pertumbuhan ekonomi daerah di Provinsi Lampung - Kurniadi, Danang; Syamsiyah, Nur; Yunarti, Yuyun (Journal of Economics Research and Policy Studies, 2025)
The goal of this study is to examine the relationship between the HDI and unemployment rates, and the GDP growth rate in Lampung Province from 2020 to 2024. This quantitative study integrates cross-sectional data from 15 cities and districts in Lampung Province with time-series data spanning five years. The CBS (Central Bureau of Statistics) was consulted for the data retrieval. The Fixed Effect Model (FEM) was chosen as the best estimating model after the Chow and Hausman tests proved its appropriateness. The results indicate that the Human Development Index has a positive impact on regional economic growth. In contrast, unemployment has little bearing on Lampung Province's economic growth. The findings suggest that healthcare and education reforms have the potential to increase productivity and drive regional economic growth. Additionally, although it is not the primary factor, the combined effect of the Human Development Index and unemployment rates has a significant influence on the economic growth of Lampung Province.